Basilar artery plaque distribution is associated with pontine infarction and vertebrobasilar artery geometry - Zheng, Jinmei; Sun, Bin; Lin, Ruolan; Teng, Yongqi; Zheng, Enshuang; Zhao, Xihai; Xue, Yunjing (Frontiers in Neurology, 2023)
Background Basilar artery (BA) atherosclerosis is a common cause of posterior-circulation ischemic stroke. In this study, we investigate the relationship between BA plaque distribution and pontine infarction (PI), further, explore the influence of vertebrobasilar artery (VBA) geometries on BA plaque distribution. Materials and methods 303 patients were performed with MRI in this study, patients were divided into three groups: no cerebral infarction (NCI), anterior circulation cerebral infarction (ACCI), and posterior circulation cerebral infarction (PCCI), the VBA geometry was classified into four configurations: Walking, Tuning Fork, Lambda, and No Confluence. The AP-Mid-BA, Lateral-Mid-BA, and VA-BA angles were measured on three-dimensional time-of-flight magnetic resonance angiography. Patients underwent high-resolution magnetic resonance imaging to evaluate the BA plaque distribution (either anterior, posterior, or lateral wall). Acute and subacute cerebral infarction [including pontine infarction (PI)] were identified by T2 weighted imaging-fluid-attenuated inversion recovery and diffusion-weighted imaging. Results The presence of BA plaque (P < 0.001) were associated with PCCI. Eighty-six patients all with BA plaque were further analyzed, compared with patients without pontine infarction, patients with pontine infarction were more likely to have plaque distributed at the posterior wall (P = 0.009) and have larger VA-BA anger (38.72° ± 26.01° vs. 26.59° ± 17.33°, P = 0.035). BA plaques in patients with pontine infarction were more frequently located at the posterior wall (50.00%) than at the anterior (10.00%) and lateral (37.50%) walls (P = 0.028). In Walking, Lambda and No Confluence geometry, BA plaques were prone to located at the lateral wall than at the anterior and posterior walls (all P ≤ 0.05). In the Tuning Fork group, BA plaques were evenly distributed. Conclusion BA plaque was related to PCCI, BA plaque distribution was associated with PI, and VBA configuration strongly influences BA plaque distribution.